[Image 54] - Smith, Captain Sir William [?ob. 1732] (My University, 1802)
Captain Sir William Smith was in the Royal Engineers.
Original drawings and paintings of Ireland and Scotland, vol 1
View from the counterscarp of an Old Spanish Keep in a redout on the hill in (what is improperly called the Isle of Burt) drawn by Capt. Sir Wm Smith in 1802.
Keywords: Island of Burt; Fortification; Architectural drawings; Ireland -- Antiquities -- Pictorial works; Donegal (Ireland : County) -- Pictorial works; Inishowen Peninsula (Ireland) -- Pictorial works; Landscapes (Representations) 1800-1810